NUTRITIONAL COMPOSITION AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS) ANALYSIS OF METHANOL LEAF EXTRACT OF Terminalia ivorensis - Enadeghe, Rosephine; Omoregie, A. E. (FUDMA JOURNAL OF SCIENCES, 2023)
Terminalia ivorensis (TI) is used in West African ethnomedicine for the treatment of ulcers, malaria, inflammation, and wounds. Despite its widespread use, its nutritional status remains largely undetermined. This study was undertaken with the aim to evalute the nutritional and phytochemical composition of TI. Proximate analysis of the methanol leaf extracts of TI was carried out using the AOAC methods. Elemental analysis of the methanol leaf extracts of the plant was also carried out using an Atomic Absorption Spectrometer (AAS). Identification and quantification of the bioactive components were determined by Gas Chromatography-Mass Spectrometry (GC-MS) single-phase ion mode. Spectra from detected compounds were matched with known compounds of the National Institute of Standards and Technology (NIST). Proximate analysis reveals that it is rich in primary nutrients such as carbohydrates (37.70±0.05%), proteins (10.94±0.03%), fats (7.97±0.12%), fibre (0.95±0.01%), ash (1.42±0.01%) and moisture content (41.02±0.21%). Mineral analysis of the extract revealed the presence of essential minerals such as calcium (641.2±1.20 mg/100g), copper (6.28±0.02 mg/100g), magnesium (186.16±0.29 mg/100g), iron (17.13±0.06 mg/100g), manganese (3.47±0.01 mg/100g), and zinc (3.82±0.01 mg/100g), which are essential for the metabolic processes and pregnancy. Forty-Seven (47) phytochemical compounds were detected by GC-MS including 1, 2, 3- Benzenetriol (26.31%), Diethyl Phthalate (14.93%), D-Allose (6.96%), Anhydro-.alpha-d-galactofuranose (5.09), Glycerin (6.28%) as the most predominant. The study revealed that Terminalia ivorensis could be a useful source of nutrients, minerals, and several helpful bioactive compounds that may serves as potential drug target needed for drug development